Current challenges and prospects of renewable energy in the Russian Federation - V. D. Klyonov (Вестник университета)
Since 2013, renewable energy has been actively developing in the Russian Federation (hereinafter referred to as RF, Russia) with the help of the programme for support of the renewable energy sources (hereinafter referred to as RES) – CSA RES 1.0 (CSA – capacity supply agreement). The second stage will start in 2025, in connection with which the article presents the intermediate results of the programme. It is noted that, despite the successes in the basic elements of the industry, a number of systemic problems and unaccounted factors can become a problem for its further effective development and lead to the development of an independent industry from state support and subsidies. The objective of the study is an analysis of the current tasks and prospects of the RES field. Particular attention is paid to the following issues: integrating the RES in the existing energy system, increasing generation efficiency, expanding the list of relevant types of RES and prospects for the development of microgeneration against the background of a growing labour shortage. An analysis of the listed problems allows us to conclude that it is necessary to solve some of them – systemic ones, those that are beyond the scope of the industry. One of the key conditions for the formation of a self-sufficient renewable energy sector in the RF is the need for a comprehensive provision that complies with current global trends, its specifics and a wide range of socio-economic factors in Russia.